2014
DOI: 10.1080/00313831.2014.904417
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gender Inequalities in the Rank of Full Professor

Abstract: This article examines whether age, work-related, and family-related predictors explain differences in the academic advancement of women and men in Iceland. Survey data were analyzed by binary logistic regression. The findings put that women climb the academic career ladder at a slower pace than men. This finding puts one of the widely known excuses for the underrepresentation of women in full professor positions into jeopardy, namely that this is because of family responsibilities. Work-related variables expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 46 publications
0
40
0
1
Order By: Relevance
“…Indeed women are promoted more slowly through academia [27]. In Japan, parental and marital status help explain gender differences in promotion rates [27], while in Scandinavia they do not [28].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed women are promoted more slowly through academia [27]. In Japan, parental and marital status help explain gender differences in promotion rates [27], while in Scandinavia they do not [28].…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline appears to leak, and at its upper limits, an increasing number of women have been flushed out for one reason or another; hence the term leaky pipeline (Blickenstaff, 2005). Research in the Icelandic academia has found that the pipeline is leaking and fewer women reach the position of full professor (Heijstra et al, 2015).…”
Section: Metaphors Relating To Obstaclesmentioning
confidence: 99%
“…It is a good sign that Italian female applications to the 2012 University habilitation are now the majority at the associate professor level for about one quarter of the sub-fields, including popular subjects such as molecular biology, human anatomy and biochemistry. This result does not rule out that gender bias might still operate in these fields [61], so that it is important to carry on removing barriers to women careers also in academic fields where female researchers are now the majority of applications to the University habilitation [62][63][64][65]. Further research could investigate gender bias in (1) how long researchers stay in the same academic position without career development, and (2) application success rates of researchers participating to the national habilitation competition with or without a tenure track or a permanent position.…”
Section: Discussionmentioning
confidence: 99%